Perubahan Respon Fisiologis BBLR setelah Perawatan Metode Kanguru di Kota Palembang - Nurcahayati, Nurcahayati; Girsang, Bina Melvia; Wahyuni, Dian (Jurusan Keperawatan FIKES UNSOED, 2016)
The main cause of neonatal mortality is low birth weight, especially in developing countries. Kangaroo mother care is one of an effective care for low birth weight infants. The purpose of the study was to identify the effect of the kangaroo mother care on physiology response of low birth weight infants in Palembang city. The study design was one-group pre and post-test with accidental sampling technique. The research was conducted on 17 babies with low birth weight (<2500 grams) in Palembang with the implementation of research in the November - December 2015. Descriptive data processing and statistical analysis using Friedman. Statistical analysis was performed with SPSS software ver.23.The result of the study was found that there were the are significant differences between before and after kangaroo mother care intervention on body temperature, respiratory rate and heart rate (p value<0.001). Kangaroo mother care may be applied as an alternative treatment for the mother in the care of low birth weight infants at home independently